PENGARUH FINANCING TO DEPOSIT RATIO, NON-PERFORMING LOAN, DAN BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL TERHADAP RETURN ON EQUITY - Jumanta; Hanifah; Mike Mega Rahayu (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to prove that whether there is a significant effect of Financing to Deposit Ratio (FDR), Non-Performing Loan (NPL), and Operating Costs to Operating Income (BOPO) on Return On Equity (ROE), both partially and simultaneously in Banking Companies Listed on the IDX Period 2018-2022. The data in this study used secondary data in the form of financial reports obtained through the Indonesia Stock Exchange website www.idx.co.id, with a sampling technique using purposive sampling resulting in a total sample of 22 banking companies. The data prerequisite test uses a classic assumption test consisting of normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. While the data analysis technique uses multiple linear regression analysis, correlation test, coefficient of determination test, partial t test, and simultaneous F test. The results of the study show that the FDR variable has a positive and significant effect on ROE partially, NPL and BOPO have a negative and significant effect on ROE partially, and FDR, NPL, and BOPO have a significant effect on ROE simultaneously.